Antifungal amides from Piper arboreum and Piper tuberculatum - da Silva, R. V.; Navickiene, HMD; Kato, M. J.; Bolzani, Vanderlan da Silva [UNESP]; Meda, C. I.; Young, MCM; Furlan, Maysa [UNESP] (Elsevier B.V., 2002)
In continuation of our study of the Piperaceae we have isolated several amides, mainly those bearing isobutyl, pyrrolidine, dihydropyridone and piperidine moieties. Bioactivity-guided fractionation of extracts from leaves of Piper arboreum yielded two new amides, N-[10-(13,14-methylenedioxyphenyl)-7(E),9(Z)-pentadienoyl]-pyrrolidine (1), arboreumine (2) together with the known compounds N-[10-(13,14-methylenedioxyphenyl)-7(E)-pentaenoyl]-pyrrolidine (3) and N-[10-(13,14-methylenedioxyphenyl)-7(L, 9(E)-pentadienoyl]-pyrrolidine (4). Catalytic hydrogenation of 3 yielded the amide iV-[10-(13,14-methylenedioxyphenyl)-pentanoyl]-pyrrolidine (5). We also have isolated six amides (6-11) and two antifungal cinnamoyl derivatives (12, 13) from seeds and leaves of Piper tuberculatum. Compounds 1-11 showed antifungal activity as determined by direct bioautography against Cladosporium sphaerospermum while compounds 3-4 and 6-13 also showed antifungal activity against C. cladosporioides. (C) 2002 Published by Elsevier B.V. Ltd.
Keywords: Piper arboreum; Piper tuberculatum; Piperaceae; amides; antifungal activity